Evaluating the Factors Influencing Consumers’ Choice of Shopping Destination: A Study of Bhatbhateni Supermarket, Bharatpur, Nepal - Manandhar, Jamuna; Kafle, Sarad Chandra (Nepal Journal of Multidisciplinary Research, 2023)
When deciding on where to shop, multiple factors play a crucial role, which can be broadly categorized into three main groups: tenant mix, access convenience, and ambience. This research paper evaluates factors influencing consumers' choice of shopping destination, focusing on Bhatbhateni Supermarket in Bharatpur, Nepal. A survey of 120 respondents shows that consumers prioritize product quality, price, location, store layout and design, customer service, and promotions when selecting a shopping destination. The choice of shopping destination is notably linked to demographic factors such as age, caste, place of residence, educational attainment, and income source, while factors such as gender and marital status did not emerge as significant indicators.. The results of this research paper have practical implications for retailers seeking to attract and retain customers in competitive markets like Nepal. By understanding consumers' preferences and decision-making processes, retailers can develop effective marketing strategies and enhance customer satisfaction. The study also provides insights for future research on this topic, emphasizing the importance of further understanding consumers' shopping behavior in the retail sector.